2017
DOI: 10.2134/jeq2016.11.0433
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Species of Phosphorus and Zinc in Water‐Dispersible Colloids from Swine Manure Compost

Abstract: The release of phosphorus (P) and zinc (Zn) from swine manure compost and from soils applied with swine manure compost can be accelerated by colloidal particles. This study investigated the concentrations and chemical species of P and Zn in waterdispersible colloids (WDCs) collected from swine manure compost by using X-ray absorption fine structure (XAFS) spectroscopy. A filtration and ultracentrifugation process was used to separate and collect WDCs (20-1000 nm) from the bulk swine manure compost (<2 mm). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…For instance, SM3 soil (2.4 g kg –1 ) contained two times greater WDC than SM1 soil (1.2 g kg –1 ) (Table S3). A similar amount of WDC was reported in paddy soils (0.8–2.2 g kg –1 , Liang et al), an upland soil (3.8 g kg –1 , Liu et al), and SM compost (2.7 g kg –1 ). The elements consisting of WDC were mainly Si, Al, and Fe for CF soil, and the contribution of C to the constituents of WDC increased notably in the soils treated with continual SM application (Table S3).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…For instance, SM3 soil (2.4 g kg –1 ) contained two times greater WDC than SM1 soil (1.2 g kg –1 ) (Table S3). A similar amount of WDC was reported in paddy soils (0.8–2.2 g kg –1 , Liang et al), an upland soil (3.8 g kg –1 , Liu et al), and SM compost (2.7 g kg –1 ). The elements consisting of WDC were mainly Si, Al, and Fe for CF soil, and the contribution of C to the constituents of WDC increased notably in the soils treated with continual SM application (Table S3).…”
Section: Resultssupporting
confidence: 76%
“…8,9 A notable accumulation of P and Zn was found in the WDC fraction of soil and SM compost compared with those bulk samples. 4,10 With the use of synchrotron-based XAFS spectroscopy, these studies revealed the contrasting differences in chemical species of P and Zn between bulk soil and WDC phases, suggesting the relevance of the WDC fraction for elucidating the mobility and potential bioavailability of elements in soils. Despite the importance of WDC in the transport and bioavailability of elements, previous studies have mainly focused on the bulk soil, particulate, and dissolved fractions (operationally defined as a <0.45 mm fraction) while neglecting colloidal fractions in the soil.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The second Zn species was another form of Zn phosphate: organic Zn phosphate (15% in SS) or crystalline Zn phosphate (8% in PM). Hopeite (crystalline Zn phosphate) has already been documented in previous studies as a major Zn phase in OWs. ,,,, …”
Section: Resultssupporting
confidence: 93%
“…Hopeite (crystalline Zn phosphate) has already been documented in previous studies as a major Zn phase in OWs. 15,16,18,22,43 In the present study, the amorphous Zn phosphate reference closely matched the Zn speciation of PM and SS. These findings are in accordance with those of a recent survey of Zn speciation in a large series of OW sampled in full-scale plants 13 where it was reported for the first time that the main Zn species in compost or stockpiled OW was amorphous Zn phosphate (40−100%).…”
Section: ■ Results and Discussionsupporting
confidence: 70%